Letter: is microwave ablation superior to radiofrequency ablation for early‐stage hepatocellular carcinoma?. Issue 11 (28th November 2018) - Liao, Ying‐Yang; Ge, De‐Xiang; Zhang, Xiao‐Ying
Abstract : Linked Content This article is linked to Zheng et al and Liu et al papers. To view these articles visit https://doi.org/10.1111/apt.14929 and https://doi.org/10.1111/apt.15048 .